Otimização do tratamento da insuficiência cardíaca com fração de ejeção reduzida com fármacos modificadores de prognóstico - Silva-Cardoso, José (2021)
Funding Information: Medical writer Duarte Oliveira (W4Research) collaborated in the preparation of this article, with financial support from Novartis Portugal. This article contains the authors? opinion on the scientific contents addressed, which are expressed independently of Novartis. Novartis did not participate in the design, discussion of, or writing of this paper. Funding Information: Medical writer Duarte Oliveira (W4Research) collaborated in the preparation of this article, with financial support from Novartis Portugal. This article contains the authors’ opinion on the scientific contents addressed, which are expressed independently of Novartis. Novartis did not participate in the design, discussion of, or writing of this paper. Funding Information: J.S.C. has consulted and received speaker fees, or advisory board participation fees or investigational grants from Abbott, AstraZeneca Pharmaceuticals, Bial, Boehringer Ingelheim, Menarini, Merck Serono, Merck Sharp & Dohme, Novartis, Orion, Pfizer, Sanofi, Servier and Vifor Pharma. C.F. has received speaker and consultancy fees, advisory board participation fees, or investigational grants from Amgen AstraZeneca, Bayer, Bial, Boehringer Ingelheim, Merck Serono, Novartis, Orion, Pfizer, Roche Diagnostics, Servier, Vifor PHarma. F.F. has received speaker and consultancy fees or advisory board participation fees from AstraZeneca, Novartis, and Servier. J.M. has received speaker and consultancy fees, advisory board participation fees or investigational grants from AstraZeneca, Bayer Healthcare, Bial, Ferrer, Menarini, Merck Sharp and Dhome, Merck Portugal, Novartis, Pfizer/BMS, and Servier J.F. reports consultancy and lecture fees from Amgen, Astra-Zeneca, Boehringer Ingelheim and Novartis. D.B. has received speaker and consultancy fees, advisory board participation fees or investigational grants from Amgen, AstraZeneca Pharmaceuticals, Boehringer Ingelheim, Linde Saúde, Merck Portugal, Novartis, Orion, Pfizer, Roche Diagnostics, Servier, and Vifor Pharma. Publisher Copyright: © 2021 Sociedade Portuguesa de Cardiologia